Respuesta :

Answer: option C

y = - x/2 + 1

Step-by-step explanation:

The equation of a straight line can be represented in the slope-intercept form, y = mx + c

Where c = intercept

Slope, m =change in value of y on the vertical axis / change in value of x on the horizontal axis

change in the value of y = y2 - y1

Change in value of x = x2 -x1

y2 = final value of y

y 1 = initial value of y

x2 = final value of x

x1 = initial value of x

Looking at the table given,

y2 = - 1

y1 = 2

x1 = - 2

x2 = 4

Slope, m = (-1 - 2)/(4 - - 2) = - 3/6 = -1/2

To determine the intercept, we will substitute m = - 1/2, y = 2 and x = - 2 into y = mx + c. It becomes

2 = -1/2× - 2 + c

2 = 1 + c

c = 2 - 1 = 1

The equation becomes

y = - x/2 + 1